Faktor-Faktor yang Mempengaruhi Self-esteem pada Mahasiswa: Tinjauan Pustaka - ANGGITA DERIZKY VIRGINIA; Rika Lisiswanti; Sutarto; Ari Wahyuni (Medula, 2024)
Self-esteem is a concept that everyone needs in life that includes an individual's subjective evaluation of their worth. Selfesteem can be defined as a person's perception of themselves, both positive and negative. Studies have shown that selfesteem has a tremendous impact on many important aspects of life, including relationships and job satisfaction, employment status, physical and mental health. In the condition of students with low self-esteem, it can affect their academic life, social life, and mental state which can cause stress to severe depression. Based on previous research, it can be seen that there are still many students who have low self-esteem. Therefore, this study aims to analyze the various factors that influence self-esteem in college students. In this study, researchers used the literature study method by compiling and analyzing fourteen articles. The results of the articles that have been reviewed, concluded that there are several factors that can affect the level of self-esteem of college students. High or low levels of self-esteem in students can be caused by a combination of family factors such as parental attention and education, academic factors such as the student's cumulative grade point average and other academic achievements, then social factors such as support from friends and their college environment, and psychological factors such as stress and depression.